2002
DOI: 10.1164/rccm.200202-090oc
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Polymorphism in the RANTES Gene Promoter Is Associated with the Development of Late-Onset Asthma

Abstract: The CC chemokine regulated upon activation, normal T-cell exsome 17q (5,6), where the gene encoding RANTES is located, the RANTES promoter region (7, 9), whereas another ge-83 middle-onset patients with asthma (onset at 20 to 40 years of netic study found a significant association of the Ϫ403A allele age), and 98 early-onset patients with asthma (onset at less than with atopy and asthma in adults (10). 20 years of age). The Ϫ28G allele was significantly associated with late-onset asthma (odds ratio ϭ 2.033; 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 33 publications
4
74
1
1
Order By: Relevance
“…In conjunction with this result, the -403A allele was suggested to be associated with an increased susceptibility to both atopy and asthma [16]. However, Hizawa et al [27] reported that the -403A allele was not associated with any of the asthma subgroups, and our results also showed that the RANTES -403 G[A polymorphism was not correlated with asthma susceptibility or asthma-related phenotypes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In conjunction with this result, the -403A allele was suggested to be associated with an increased susceptibility to both atopy and asthma [16]. However, Hizawa et al [27] reported that the -403A allele was not associated with any of the asthma subgroups, and our results also showed that the RANTES -403 G[A polymorphism was not correlated with asthma susceptibility or asthma-related phenotypes.…”
Section: Discussionsupporting
confidence: 75%
“…It has also been reported that the -28G allele elevates promoter activity and increase RANTES protein expression in the functional study [14]. In addition, Hizawa et al [27] suggested that mononuclear cells from subjects who carried the -28G allele produced significantly greater levels of RANTES protein than cells from subjects who did not carry this allele. From these findings it seems reasonable to assume that increased concentration of RANTES in asthmatic children carrying the - AA = atopic asthma; NAA = nonatopic asthma; NC = normal controls; n = number of patients; q = minor allele frequency a Each p value was calculated with codominant (c), dominant (d), and recessive (r) models.…”
Section: Discussionmentioning
confidence: 91%
“…However, there are population differences in the allelic frequencies, and possible contributions to allergic disease, of the two identified promoter polymorphisms as seen in the very low rates for the À28C/G polymorphism in our population in comparison to Japanese and Chinese populations. 12,17 In addition to population differences in genetic and environmental contributions to disease expression, the inheritance of asthma and atopy is likely to be complex and to be confounded by relatively small contributions from a number of different genes. It is also likely to be confounded by partial penetrance, by asymptomatic carriers who have not yet been exposed to the relevant environmental hazard and by disease phenocopies.…”
Section: Discussionmentioning
confidence: 99%
“…10 Two polymorphisms , a C to G substitution at position À28 and a G to A substitution at position À403, have been identified by sequencing a 1031 bp PCR fragment of the upstream noncoding region of the RANTES gene in a case-control HIV-1 population. 11 Three haplotypes have been found in a Japanese population with allele frequencies of 0.121 for the À28C/G and 0.329 for the À403G/A polymorphism, 12 although in Caucasian populations the distribution of these two polymorphisms has been found to be different with a lower allele frequency of 0.044 and heterozygosity of 0.089 for the À28C/G polymorphism 13 and an overall frequency of 0.161 and heterozygosity of 0.211 for the À403 G/A polymorphism. 14 The À403G/A point mutation results in a new consensus element for the GATA transcription factor family, 15 which suggests a role in the differential regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…We and others reported an association between the chemokine polymorphism CCL5 (G-403A), which increases constitutive transcription activity by a factor of 8, 5,6 and asthma. [7][8][9] However, the absence of an association between asthma and the deletion of the functional allele in CCR5-D32, the principal CCL5 receptor, 10,11 suggests that other CCL5 receptors may be involved in this disease.…”
Section: Introductionmentioning
confidence: 74%